Rescue archaeological excavations at Most na Soči in the year 2001: The sites of Maregova guna, Štulčev kuk and Plac - Mlinar, Miha; Klasinc, Rok; Knavs, Martina (Arheološki vestnik, 2008)
In the year 2001 the museum of Tolmin, as agreed with the Institute for the Protection of the Cultural Heritage of Slovenia (ZVKDS), Nova Gorica Regional Unit, carried out the archaeological supervision during the building and partial reconstruction of the canal network at Most na Soči. Even before this supervision the sites of Maregova guna and Štulčev kuk, which belong within the complex of the settlement, had been archaeologically investigated. At Maregova guna a number of Iron Age building remnants with small finds were uncovered. At Štulčev kuk the construction elements of a building were investigated, which apparently dates from late La Tène or early Roman times. The archaeological supervision was also carried out during other construction activities at Most na Soči.